Vibration of 2D-FGSW timoshenko beams under a moving harmonic load - Ninh, Vu Thi An; Anh, Le Thi Ngoc; Kien, Nguyen Dinh (Vietnam Journal of Science and Technology, 2020)
Vibration of two-directional functionally graded sandwich (2D-FGSW) Timoshenko beams under a moving harmonic load is investigated. The beams consist of three layers, a homogeneous core and two functionally graded skin layers with the material properties continuously varying in both the thickness and length directions by power functions. A finite element formulation is derived and employed to compute the vibration characteristics of the beams. The obtained numerical result reveals that the material inhomogeneity and the layer thickness ratio play an important role on the natural frequencies and dynamic response of the beams. A parametric study is carried out to highlight the effects of the power-law indexes, the moving load speed and excitation frequency on the vibration characteristics of the beams. The influence of the beam aspect ratio on the vibration of the beams is also examined and discussed.